Per Hage & Frank Harary: Island Networks. Communication, Kinship, and Classification Structures in Oceania. - Liep, John (Tidsskriftet Antropologi, 1998)
Communication, Kinship, and Classification Structures in Oceania. Anmeldes af John Liep.